2021
DOI: 10.1051/0004-6361/202140676
|View full text |Cite
|
Sign up to set email alerts
|

Testing the magnetic flux paradigm for AGN radio loudness with a radio-intermediate quasar

Abstract: For understanding the diversity of jetted active galactic nuclei (AGN) and especially the puzzling wide range in their radio loudness, it is important to understand what role the magnetic fields play in setting the power of relativistic jets in AGN. We have performed VLBA phase-referencing observations of the radio-intermediate quasar IIIZw 2 to estimate jet magnetic flux by measuring the core-shift effect. Multi-frequency observations at 4 GHz, 8 GHz, 15 GHz, and 24 GHz were made using three nearby calibrator… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 84 publications
1
13
0
Order By: Relevance
“…One possibility is that the central engines in high-redshift AGNs have not yet reached the magnetically arrested disk (MAD) state (Narayan et al 2003). A similar case can be seen in the nearby radio-intermediate quasar III Zw 2 (Chamani et al 2021). Measurements of the magnetic field strength in high-z jets and high-resolution numerical simulations would help to solve this puzzle.…”
Section: Resultsmentioning
confidence: 62%
“…One possibility is that the central engines in high-redshift AGNs have not yet reached the magnetically arrested disk (MAD) state (Narayan et al 2003). A similar case can be seen in the nearby radio-intermediate quasar III Zw 2 (Chamani et al 2021). Measurements of the magnetic field strength in high-z jets and high-resolution numerical simulations would help to solve this puzzle.…”
Section: Resultsmentioning
confidence: 62%
“…The 2D crosscorrelation technique has been widely used to align multifrequency VLBI images (e.g. Walker et al 2000;Kovalev et al 2008;Croke & Gabuzda 2008;O'Sullivan & Gabuzda 2009;Hovatta et al 2012;Pushkarev et al 2012;Kutkin et al 2014;Kravchenko et al 2016;PL19;Chamani et al 2021).…”
Section: D Cross-correlation Of the Imagesmentioning
confidence: 99%
“…Several studies have confirmed r core ∝ ν −1 obs (Lobanov 1998;Hirotani 2005;O'Sullivan & Gabuzda 2009;Fromm et al 2010Fromm et al , 2013bFromm et al , 2015Sokolovsky et al 2011;Hada et al 2011;Mohan et al 2015;Lisakov et al 2017;Pushkarev et al 2018) and the amount of core shift together with the equipartition assumption has been frequently used to infer jet magnetic field strengths (e.g. Pushkarev et al 2012;Voitsik et al 2018;Plavin et al 2019b, hereafter PL19;Chamani et al 2021). However, there is very little knowledge of the stability of the index k r over time or how this affects the inferred magnetic field strength.…”
Section: Introductionmentioning
confidence: 99%
“…Significant simplifications were adopted to obtain these results and a detailed critical discussion was presented by Gralla (Gralla, 2021). On a more general point of view, it is worth citing the Very Long Baseline Array (VLBA) study on III Zw 2 (z 0.089 8), a c-ray intermediate Seyfert (Liao et al, 2016), which revealed that the measured magnetic field in the innermost region was well below the value prescribed by the MAD model (Chamani et al, 2021). III Zw 2 has an accretion rate greater than M87 [∼ 0.04 vs. ∼ 2 × 10 −5 (Berton et al, 2015;Akiyama et al, 2019e)], which implies a likely different accretion disk, much more radiatively efficient.…”
Section: High-resolution Radio Observationsmentioning
confidence: 99%